CHARACTERISTICS OF INTELLECTUAL LABOUR ORGANIZATION IN INFORMATION SOCIETY - A. Devyatiarova (Вестник университета)
Characteristics of tertiary sector of the economy and employment evolution are given. Types and features of intellectual labour organization are analyzed. Possibilities of labour organization development in today’s world are reviewed.